Power maximization from resonant electromagnetic vibration harvesters feeding bridge rectifiers. (7th October 2018) - Costanzo, Luigi; Lo Schiavo, Alessandro; Vitelli, Massimo
Summary: In this paper, it is shown that, for resonant electromagnetic vibration energy harvesters (REVEH) feeding diode bridge rectifiers, it is possible to quantify how close the ideal load condition is to the actual load condition. For this purpose, a new figure of merit, the REVEH exploitation factor (REF), is introduced. The higher the REF, the higher the REVEH exploitation. Moreover, by using the REF, a suitable technique for increasing the extracted power in a frequency region of interest is investigated. This is the frequency region where a significant energy content of the input vibrations is present. The investigated technique is based on the proper insertion of additional non‐dissipative components (capacitors or inductors) between the REVEH coil and the bridge rectifier. Experimental results confirm the validity of the theoretical analysis. Abstract : For resonant electromagnetic vibration energy harvesters, a new figure of merit is introduced in order to quantify how close the ideal load condition is to the actual load condition. Moreover, this figure of merit is used to analyse a technique aimed at increasing the extracted power in the frequency region of interest. The technique is based on the insertion of additional non‐dissipative components. Experimental findings confirm the validity of the theoretical analysis.